The clinical significance of open vs. minimally invasive surgical approaches in the management of thymic epithelial tumors and myasthenia gravis - Alcasid, Nathan J.; Vasic, Ivana; Brennan, Phillip G.; Velotta, Jeffrey B. (Frontiers in Surgery, 2024)
Though advancements have been made in the pharmacologic treatment of myasthenia gravis (MG), surgical resection is not only an option as a last line of defense for those patients who do not respond to medical therapy but also remains vital for those with thymic epithelial tumors (TET). While prior studies have shown the potential superiority of minimally invasive approaches via robotic- and video-assisted thoracoscopic surgery (RATS/VATS) for thymectomy compared to open surgery, in the setting of malignancies, this outcome delineation is controversial. As RATS/VATS may be associated with less post-operative complications in the treatment of TET, some surgeons argue that the open approach is necessary for complete resection (R0 resection) and to prevent potential seeding of the malignancy. In this review article, we will compare the efficacy and implications of the different surgical approaches and techniques themselves in performing a thymectomy for autoimmune and oncologic pathologies.